Varying effect of biochar on Cd, Pb and As mobility in a multi-metal contaminated paddy soil - Yin, Daixia; Wang, Xin; Chen, Can; Peng, Bo; Tan, Changyin; Li, Hailong (Chemosphere (Oxford), 2016)
Cd, Pb and As stand as the most prominent contaminants prevailing in Chinese soils. In the present study, biochars derived from water hyacinth (BCW) and rice straw (BCR) were investigated regarding their applicability and durability in soil Cd, Pb, and As immobilization under acid precipitation. Total Cd, Pb, and As in both BCs were below the maximum allowed threshold according to biochar toxicity standard recommended by International Biochar Initiative. To evaluate BCs effect on Cd, Pb, As bioavailability and mobility, CaCl2, KH2PO4 and SPLP extractions were firstly carried out. In neutral extraction with CaCl2 and KH2PO4, significantly reduced Cd/Pb concentrations in CaCl2 extract along with elevated KH2PO4-extractable As were recorded with either BC at 2% or 5%. In SPLP with simulated acid rainwater as extractant, comparable Cd, Pb and As levels were determined in SPLP extract with 2% BCW, while slight to significant increase in SPLP-Cd, Pb or As was recorded with other treatments. Longer-term leaching column test further confirmed the high durability of 2% BCW in Cd immobilization under continuous acid exposure. In parallel, little increase in As concentrations in eluate was determined with 2% BCW compared to no-biochar control, indicating a lowered risk of As mobilization with acid input. However, remarkably higher Pb in leachate from both BCW-only control and 2% BCW-amended soils were noticed at the initial stage of acid leaching, indicating a higher acid-solubility of Pb minerals in BCW (most probably PbO) than in tested soil (PbO2, PbAs2O6). Taken together, BCW exhibited important potential for soil Cd sequestration with little effect on As mobilization under acid precipitation. But it may simultaneously load highly acid-soluble Pb minerals into soils, resulting in elevated Pb mobility upon acid exposure. Therefore, more stringent threshold for Pb content in biochar need to be put forward to secure biochar application in soils subject to anthropogenic acidification. [Display omitted] •Prolonged Cd immobilization was achieved with BCW under acid precipitation.•BCW application increased soil Pb leachability upon acid exposure.•Higher KH2PO4-extractable As was obtained with BCW addition.•BCW incorporation induced little increase in As mobilization with acid input.•More stringent Pb threshold allowed in biochar need to be proposed.